Developing E-Comics Based on Central Kalimantan Cultural Wisdom to Enhance the Local Creative Economy - Arna Purtina; Mohamad Nor Aufa; Muqor Rama Hasanah (Universitas Lambung Mangkurat, 2026)
This study was motivated by the limited availability of learning media that integrate Central Kalimantan's local wisdom with creative economy learning in an engaging and contextual way. It aimed to develop an e-comic based on Central Kalimantan cultural wisdom and to examine its feasibility and student responses as a learning and promotional medium for the creative economy. The study used a research and development approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The cultural content focused on Dayak traditional crafts, especially rattan weaving and woven products, presented through a visual narrative. Expert validation produced a mean score of 3.78, indicating that the e-comic was highly feasible in terms of appearance, content, language, and goal relevance. Student responses yielded a mean score of 3.6, indicating positive acceptance in terms of interest, usability, and relevance to the material. These findings show that the developed e-comic is feasible and practical for use in creative economy learning while also introducing local cultural and economic potential. The study implies that culturally grounded digital media can support contextual learning, local culture promotion, and awareness of community-based creative economy opportunities